Exercise intensity-specific changes to cerebral blood velocity do not modulate a postexercise executive function benefit - Tari, B; Shirzad, M; Behboodpour, N; Belfry, GR; Heath, M (Elsevier, 2021)
Executive function is transiently improved (i.e., <60-min) following a single bout of aerobic exercise. A candidate mechanism for this improvement is an exercise-mediated increase in cerebral blood flow (CBF). Further, it has been proposed that an increase in CBF across the continuum of increasing exercise intensities improves the magnitude of a postexercise executive function benefit (i.e., drive theory); however, this proposal has not been empirically tested. Here, participants completed four experimental sessions: a V̇O2peak test to determine cardiorespiratory fitness and estimated lactate threshold (LT), followed by separate 10-min sessions of light- (i.e., 25 W), moderate- (i.e., 80% estimated LT), and heavy-intensity (i.e., 15% of the difference between LT and V̇O2peak) aerobic exercise. An estimate of CBF during exercise was achieved via transcranial Doppler ultrasound and near-infrared spectroscopy to quantify blood velocity (BV) through the middle cerebral artery and deoxygenated hemoglobin (HHb), respectively. Executive function was assessed before and after each session via the executive-mediated antisaccade task (i.e., saccade mirror-symmetrical to a target). Results demonstrated that BV increased in relation to increasing exercise intensity, whereas HHb decreased by a comparable magnitude independent of intensity. In terms of executive function, null hypothesis and equivalence tests indicated a comparable magnitude postexercise reduction in antisaccade reaction time across exercise intensities. Accordingly, the magnitude of CBF change during exercise does not impact the magnitude of a postexercise executive function benefit.